Chinese attitudes toward nuclear weapons : China and the United States during the Korean War - Ryan, Mark A.; ProQuest (firma) (London : Routledge, Taylor & Francis Group, 2016)
This book examines the crucial formative period of Chinese attitudes toward nuclear weapons - the immediate post-Hiroshima/Nagasaki period and the Korean War. It provides a detailed account of U.S. actions and attitudes during this period and China's response, which was especially acute after both countries had entered the Korean conflict as enemies. This response dispels some of the myths that have long existed regarding China's perceptions of nuclear war.
Part I, Prewar and Early Korean War -- Part II, Korean Stalemate -- Part III, Chinese Defenses and the Korean Armistice
Obsahuje bibliografické odkazy
Elektronická reprodukce.
Keywords: 20. století; korejská válka (1950-1953); vojenská politika -- Čína -- 20. století; vojenská politika -- Spojené státy americké -- 20. století; jaderné zbraně -- Čína -- 20. století; jaderné zbraně -- Spojené státy americké -- 20. století; monografie; Korean War (1950-1953); military policy -- China -- 20th century; military policy -- United States -- 20th century; nuclear weapons -- China -- 20th century; nuclear weapons -- United States -- 20th century; monographs; e-knihy online; e-knihy online; e-books online; e-books online